Effect of cattle liquid manure fertilization on the yield of grassland and density of soil oribatid mites (Acari, Oribatida) - Kruczyńska, Karolina; Seniczak, Stanisław (Biological Letters, 2011)
The effect of cattle liquid manure without and with Effective Microorganisms (EM) on the hay yield and density of soil Oribatida was investigated in a lowland meadow. Fertilization of the meadow with low and medium doses (30 m3·ha-1 and 60 m3·ha-1) of liquid manure increased the hay yield, more with EM than without them. However, the highest dose (90 m3·ha-1) of fertilizer did not change hay yield, as compared to the control plot. All doses of cattle liquid manure reduced the density of oribatid mites, distinctly more without EM than with them. This suggests a favourable influence of EM on these mites. Among the Oribatida, Liebstadia similis, Scheloribates laevigatus, Eupelops occultus, and Achipteria coleoptrata, were abundant, while other species were infrequent. The community of Oribatida was dominated by adults.